Environmental implications of different production systems in a Sardinian dairy sheep farm - Franca A.; Vagnoni E. (Innovation for sustainability in sheep and goats, 2019)
Sardinia (Italy) plays a relevant role on EU sheep milk production. As well as in others Mediterranean regions, contrasting dairy sheep farming systems coexist in Sardinia and an effective renovation process is needed in order to contrast the deep structural crisis. Eco-innovation of production processes and the valorisation of pasture-based livestock systems can be a key strategy to improve the farms competitiveness and to promote the typical Mediterranean dairy sheep products in a green way. For this purpose, research studies are needed in order to assess the environmental implications of Mediterranean sheep systems with a holistic and site-specific approach. The main objective of this study was to compare the environmental performances of two contrasting sheep milk production systems, by using a Life Cycle Assessment (LCA) approach. The LCA was carried out in a farm where, along ten years, a conversion from arable and irrigated crops to native and artificial pastures and a reduction of total mineral fertilizers supply occurred. The effects of the conversion on the environmental impacts were analyzed both using 1 kg of Fat and Protein Corrected Milk (FPCM) and 1 ha of surface as functional units. The LCA study highlighted that the change from a semi-intensive to a semi-extensive production system had a different effect on the environmental impacts depending on the utilized functional unit.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)